THE DEVELOPMENT OF TATABBUA IN PERSIAN TAJIKI POETRY (IN THE EXAMPLE of MUIZZI NISABURI) - Ramazon Abdulloyev (American Journals, 2023)
The article examines the evolution of tatabbu as one of the forms of manifestation of influence and creative connection between poets following Rudaki's ode "The smell of the stream of Mulian comes to everyone", and in this context, some theoretical issues and characteristics of the poems sung following this ode are discussed by Muizzi, Sanai, Maulavi. , Wassof and others, it has been compared, analyzed and evaluated, which clarifies the essence of this poetic experience and the approach to the development of tatabusarai in Tajik Persian poetry as a literary and artistic experience. Also, in the article, the social, political and cultural influencing factors of the development of tatabbuisa, its weakness and superiority are investigated in a comparative manner, and the essence of this artistic tendency is evaluated as an expression of the technical skills of tatababuisa poets and the type of artistic experiment, in this context, methods, approaches and professional consistency are evaluated. defines and confirms the poets' artistic aspirations to the lasting literary traditions.
Keywords: Travel, development, Rasul Hadizadeh, follow, follow, welcome, reply, reply Farrokhi, the rider of imagination, weight, rhyme, radif, Dr. Muhammed Mu'in Tariz, exercise, ghazal, ode, influence, Rudaki, Muizzi, Maulavi, Sanai, Wassof, etc.